PERANCANGAN BUKU INTERAKTIF SEBAGAI MEDIA MANAJEMEN STRES PADA FASE QUARTER-LIFE CRISIS - Panji Firman Rahadi; Oki Adityawan; Annita Komariati Prihandayani; William Handoko (Wacadesain, 2022)
Social media has become one of the causes of the rise in mental health problems of young adults in recent years. Quarter-Life Crisis is one of the mental health phenomena that become their problem. Lack of awareness about stress management is a problem for sufferers. The method of this research is descriptive qualitative research, the technique used in data collection based on interviewing experts in the field of psychology is the most relevant method to get maximum results for research in the field of mental health. Based on the results of the author's research, it was found that sufferers have two main problems in the career and romance aspects. Lack of information, the media, and someone who becomes a